Clinical and epidemiological features of myasthenia gravis in Chilean population. (29th May 2018) - Cea, G.; Martinez, D.; Salinas, R.; Vidal, C.; Hoffmeister, L.; Stuardo, A.
Abstract : Objective: To provide an estimated prevalence and describe the clinical features of myasthenia gravis (MG) in Chile. Method: We carried out (i) a prevalence study of MG using the capture‐recapture method and the hospital register of pyridostigmine prescription in South‐East Santiago (ii) a nationwide survey of MG patients. Results: Prevalence in adults in South‐East Santiago was estimated to be 8.36/100 000 inhabitants (CI: 95%, 7.98‐8.80). From the nationwide survey, 405 questionnaires were analysed, there was a female/male ratio of 2.2:1. The mean age of onset of symptoms was 38.7 years (range 1‐89). The onset was ocular in 46.4%, oculobulbar in 11.6%, bulbar in 8.9%, limbs in 11.6% and generalized in 21.4%. Of the 13.3% of patients who had had a diagnosis of thymoma, only four of these patients were >60 years old at onset. Thymomas were commoner in patients living in mining counties. Patients ≥60 years old at onset of MG formed 19.5% of the sample, female/male ratio 0.97:1. Associated autoimmune diseases were reported in 14% of patients and in family members of 31.8% of patients. A total of 78 patients had to change work due to MG and 68 needed help in carrying out daily activities. Conclusions: This study reduces the gap in information about MG in South America. The prevalence of MG in Chile is within the range described worldwide. We did not see an increase in male frequency in the older age of onset group and thymoma was more frequent in the fifth and sixth decades.